1998
DOI: 10.1164/ajrccm.158.6.9712073
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Deposition in Large Airways May Not Differentiate Severe Asthma from Milder Forms of the Disease

Abstract: Chronic airway inflammation and remodeling, including fibrosis, have been proposed as important contributors to asthma pathophysiology. Previous studies of airway fibrosis have been performed mainly in mild and moderate asthmatics at the subepithelial "basement membrane" (SBM) level. The current study was designed to evaluate the large airway SBM thickness and submucosal collagen deposition, as measured by three different collagen staining methods, in endobronchial biopsies from 17 severe, nine moderate, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
5
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(168 citation statements)
references
References 30 publications
13
145
5
5
Order By: Relevance
“…The lack of an association of past RBM thickness with wheeze persisting at age 5 yrs and lung function is in agreement with studies in older children and adults with asthma that were unable to demonstrate a relationship between RBM thickness, duration and severity of asthma [18,19] and lung function [18,20]. Indeed, it has been proposed that RBM thickening may be protective rather than deleterious [5,6].…”
Section: Discussionsupporting
confidence: 81%
“…The lack of an association of past RBM thickness with wheeze persisting at age 5 yrs and lung function is in agreement with studies in older children and adults with asthma that were unable to demonstrate a relationship between RBM thickness, duration and severity of asthma [18,19] and lung function [18,20]. Indeed, it has been proposed that RBM thickening may be protective rather than deleterious [5,6].…”
Section: Discussionsupporting
confidence: 81%
“…CHAKIR et al [45] described an association between disease severity and collagen deposition. In contrast, CHU et al [24] found no identifiable differences in collagen deposition or TGF-b expressing cells in the large airways of mild when compared with severe asthmatics.…”
Section: Is Remodelling Positively Correlated To Disease Severity?mentioning
confidence: 83%
“…This region, which is composed of collagen I, collagen III, collagen V, fibronectin and tenascin, and is situated just below the basement membrane, has an overall thickness of ,3-4 mm in nonasthmatics, while in asthma this is increased two-to three-fold [22,23]. Although increased collagen deposition in the lamina reticularis is a characteristic of asthma, it may not explain the differences in severity of asthma [24]. Functionally, thickening of the lamina reticularis has been linked to reduced airway distensibility and increased airflow limitation in asthma [25], suggesting that this altered structure has a negative impact on lung function.…”
Section: Thickening Of the Lamina Reticularismentioning
confidence: 99%
“…The effect on structural airway changes, the so-called airway remodelling, is less clear. These changes that include goblet cell hyperplasia (GCH), smooth muscle hypertrophy/hyperplasia, airway wall thickening and increased deposition of extracellular matrix proteins are present even in patients with mild asthma [2] and early in the disease process [3,4]. Most [5][6][7][8][9], but not all [10,11], biopsy studies show a limited effect of ICS on remodelling of asthmatic airways, possibly attributable to an effect on growth factor expression [8] or on the balance between matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 [9].…”
mentioning
confidence: 99%